2002
DOI: 10.1128/mcb.22.17.6306-6317.2002
|View full text |Cite
|
Sign up to set email alerts
|

DNA Substrate Dependence of p53-Mediated Regulation of Double-Strand Break Repair

Abstract: DNA double-strand breaks (DSBs) arise spontaneously after the conversion of DNA adducts or single-strand breaks by DNA repair or replication and can be introduced experimentally by expression of specific endonucleases. Correct repair of DSBs is central to the maintenance of genomic integrity in mammalian cells, since errors give rise to translocations, deletions, duplications, and expansions, which accelerate the multistep process of tumor progression. For p53 direct regulatory roles in homologous recombinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
268
2
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(282 citation statements)
references
References 57 publications
9
268
2
3
Order By: Relevance
“…A recent report using an ISceI endonuclease-based cell system in human leukemic and lymphoblastoid cells demonstrated that expression of wild-type P53 in P53 null cells inhibits HRR as well as microhomology-directed NHEJ. Thus, P53 may restrain DNA exchange between imperfectly homologous sequences (Akyuz et al, 2002). More studies are needed to confirm these findings using chromosomal substrates instead of DSBs generated by a rare-cutting endonuclease and under conditions when other P53 effects are controlled.…”
Section: Role Of P53 and Other Tumor Suppressors In Dsb Repairmentioning
confidence: 85%
“…A recent report using an ISceI endonuclease-based cell system in human leukemic and lymphoblastoid cells demonstrated that expression of wild-type P53 in P53 null cells inhibits HRR as well as microhomology-directed NHEJ. Thus, P53 may restrain DNA exchange between imperfectly homologous sequences (Akyuz et al, 2002). More studies are needed to confirm these findings using chromosomal substrates instead of DSBs generated by a rare-cutting endonuclease and under conditions when other P53 effects are controlled.…”
Section: Role Of P53 and Other Tumor Suppressors In Dsb Repairmentioning
confidence: 85%
“…We have previously shown that spontaneous recombination events, which are independent of any targeted cleavage but strictly associated with DNA replication, can be detected in cells carrying a stably integrated EGFP-based substrate (13,25) (Fig. 1A).…”
Section: Resultsmentioning
confidence: 99%
“…However, how these isoforms affect DNA damage repair is rarely studied. Many studies have demonstrated that full-length p53 inhibits DNA DSB repair [12][13][14]. A recent study using human cells has shown that, in response to γ-irradiation treatment, p53 pulses induce apoptosis at the early stage and postpone DNA DSB repair to the later stage [22].…”
Section: Discussionmentioning
confidence: 99%
“…The expression of p53 downstream genes triggers cell cycle arrest, DNA damage repair, apoptosis and/or senescence to ensure genome stability [7,8]. Intriguingly, p53 protein appears to promote only some DNA damage repair pathways, such as base excision repair, mismatch repair and nucleotide excision repair [9][10][11], but inhibit DNA DSB repair pathways, including the HR, NHEJ and SSA pathways [12][13][14]. It has been demonstrated that p53 exerts a direct effect on DNA DSB repair, as mutations in p53 that impair or even abolish its transcriptional activity and cell cycle regulatory capacity do not significantly affect its inhibition of HR [15][16][17].…”
Section: Introductionmentioning
confidence: 99%